Crohn's Disease of the Esophagus, Duodenum, and Stomach - Schwartzberg, David M.; Brandstetter, Stephen; Grucela, Alexis L. (Clinics in Colon and Rectal Surgery, 2019)
Upper gastrointestinal Crohn's is an under-reported, under-recognized phenotype of Crohn's disease. Routine screening in the pediatric population has shown a higher prevalence compared with adults; however, most adult patients remain asymptomatic with respect to upper gastrointestinal Crohn's disease. For the patients who are symptomatic, medical treatment is the first line of management, except for cases of obstruction, perforation, or bleeding. Though most patients respond to medical therapy, mainly steroids, with the addition of immunomodulators and more recently biologics agents, surgical intervention is usually required only for obstructing gastroduodenal disease secondary to strictures. Strictureplasty and bypass are safe operations with comparable morbidity, although bypass has higher rates of dumping syndrome and marginal ulceration in the long term. Rare cases of gastroduodenal fistulous disease from active distal disease may involve the stomach or duodenum, and esophageal Crohn's disease can fistulize to surrounding structures in the mediastinum which may require the highly morbid esophagectomy.
Keywords: Upper Gastrointestinal Crohn's Disease; gastroduodenal Crohn's disease; esophageal Crohn's disease; strictureplasty